The tumour microenvironment is immuno‐tolerogenic and a principal determinant of patient outcome in EBV‐positive diffuse large B‐cell lymphoma. (24th July 2019) - Keane, Colm; Tobin, Joshua; Gunawardana, Jay; Francis, Santiyagu; Gifford, Grace; Gabrielli, Sara; Gill, Anthony; Stevenson, William; Talaulikar, Dipti; Gould, Clare; Jain, Sanjiv; Birch, Simone; et al.
Abstract: Objective: Epstein‐Barr virus‐positive diffuse large B‐cell lymphoma (EBV ‐pos DLBCL) is a recently identified entity. Data regarding outcome to frontline immuno‐chemotherapy are conflicting. Although the prognostic impact of the tumour microenvironment (TME) in EBV ‐neg DLBCL is well‐established, it remains untested whether the TME influences survival in EBV ‐pos DLBCL. There are no data with new digital gene expression technologies that simultaneously interrogate the virus, B cells and the tumour microenvironment (TME). Methods: We used the NanoString™ platform in a population‐based cohort of 433 patients to establish if the technology could detect EBV in the tumour biopsies and to investigate the influence that EBV has on the complex tumour microenvironment of DLBCL. Results: Incidence of EBV ‐pos DLBCL was 6.9% with 5‐year survival of 65% vs 82% in EBV ‐neg DLBCL ( P = 0.018). EBV ‐pos tissues had similar expression of T‐cell genes compared to EBV ‐neg DLBCL but higher levels of the antigen‐presenting molecule B2M. This was countered by elevated PD‐L1, PD‐L2, LAG3 and TIM3 immune checkpoints and a higher CD163/CD68 "M2" macrophage score. Conclusion: In EBV ‐pos DLBCL, the TME is immuno‐tolerogenic and may explain the poor outcomes seen in this subtype of DLBCL.